Targeting ultra-high energy neutrinos with the ARIANNA experiment - Anker, A.; Barwick, S. W.; Bernhoff, H.; Besson, D. Z.; Bingefors, N.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J. C.; Lahmann, Robert; Latif, U.; Nam, J.; et al. (Advances in Space Research, 2019)
The measurement of ultra-high energy (UHE) neutrinos (E > 1016 eV) opens a new field of astronomy with the potential to reveal the sources of ultra-high energy cosmic rays especially if combined with observations in the electromagnetic spectrum and gravitational waves. The ARIANNA pilot detector explores the detection of UHE neutrinos with a surface array of independent radio detector stations in Antarctica which allows for a cost-effective instrumentation of large volumes. Twelve stations are currently operating successfully at the Moore's Bay site (Ross Ice Shelf) in Antarctica and at the South Pole. We will review the current state of ARIANNA and its main results. We report on a newly developed wind generator that successfully operates in the harsh Antarctic conditions and powers the station for a substantial time during the dark winter months. The robust ARIANNA surface architecture, combined with environmentally friendly solar and wind power generators, can be installed at any deep ice location on the planet and operated autonomously. We report on the detector capabilities to determine the neutrino direction by reconstructing the signal arrival direction of a 800 m deep calibration pulser, and the reconstruction of the signal polarization using the more abundant cosmic-ray air showers. Finally, we describe a large-scale design – ARIA – that capitalizes on the successful experience of the ARIANNA operation and is designed sensitive enough to discover the first UHE neutrino.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Antarctica; ARIANNA; Askaryan radiation; Cosmic ray; Neutrino; Radio